Respuesta :

If they are inverses, then when you have a composite function with the original and the inverse, it hits the y = x line. That is because an inverse is the original function reflected about the line y = x, and hence, the x and y-ordinates are interchanged.

Here's an example:
If [tex]f(x) = 3x + 1[/tex], find [tex]f^{-1}(x)[/tex] and prove that there is an inverse function.

Step 1) Interchange the x and y-values: [tex]x = 3y + 1[/tex]
Step 2) Find an equation with y being the subject: [tex]y = \frac{x - 1}{3}[/tex]

Now, that becomes your inverse function. So, if we find [tex]f(f^{-1}(x))[/tex] or [tex]f^{-1}(f(x))[/tex], then that should bring us back to x; ie there is a one-to-one function.

[tex]f(f^{-1}(x)) = 3(\frac{x - 1}{3}) + 1[/tex]
[tex]= x - 1 + 1[/tex]
[tex]= x[/tex]

Thus, there is an inverse function at [tex]f^{-1}(x) = \frac{x - 1}{3}[/tex]
ACCESS MORE